Madrasah Principal's efforts to Improve the Literacy Culture of Students in Madrasahs Based on Islamic Boarding Schools - Pusvyta Sari; Mar’atul Uliyah; Ahmad Murod (Annusfy : Journal of Multidisciplinary Research, 2026)
Literacy is an important skill for facing the challenges of the times. This study aims to determine how the principal of the school strives to improve the literacy of students at the MA Unggulan Al Imdad Yogyakarta Islamic boarding school, as well as the supporting and inhibiting factors. This study uses a descriptive qualitative approach, with a case study to identify and describe the experiences of madrasah principals in fostering a culture of literacy at Madrasah Aliyah Unggulan Al Imdad. Data collection methods include interviews, observation, and documentation. The results of the study show that the efforts made include developing madrasah flagship programs (tahfidzul Qur'an, reading classical Islamic texts, proficiency in Arabic, proficiency in English) and developing pro-literacy extracurricular activities (journalism, literature classes, research assistance, literacy competitions, and publication of works). Supporting factors for these literacy cultivation efforts included the enthusiasm of madrasah residents in literacy activities, support and cooperation with stakeholders both inside and outside the madrasah environment who were able to motivate them to improve literacy and produce works, and the availability of equipment and infrastructure to support pro-literacy extracurricular activities. Meanwhile, the inhibiting factors include: limited budget, limited time for literacy program mentoring, and the lack of integration of literacy learning in madrasahs and Islamic boarding schools. There is a lack of varied, high-quality reading materials, no guidance on how to use technology more effectively, and literacy policies and programs are not yet systematically and sustainably organized.